Design and Implementation of Disc Sector Slot on a 4x2 Microstrip Array Antenna Using the Truncated Corner Method for 2.4 GHz Frequency - Yaqub, Aditya Verdianda; Koesmarijanto, Koesmarijanto; Hudiono, Hudiono (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
One widely used antenna type is the microstrip antenna due to its small size, simple fabrication, compact structure, and low cost. However, microstrip antennas suffer from inherent limitations such as narrow bandwidth, low gain, and poor directivity. This research investigates the effect of adding a disc sector–shaped slot to improve antenna gain. The antenna is designed to meet specifications of VSWR less than 2, return loss below −10 dB, and gain greater than 3 dB. The objective is to enhance gain performance and demonstrate the effectiveness of slot addition within the 2401–2495 MHz frequency range for Wi-Fi applications. Simulation and measurement results show that the microstrip antenna with a disc sector slot achieves a gain of 12.55 dBi at 2448 MHz and operates effectively within the 2421–2467 MHz range. The antenna exhibits a return loss of −17.37 dB and a VSWR of 1.31. Furthermore, for Wi-Fi implementation at 2.4 GHz, the antenna achieves a received power level of −63 dBm at a distance of 20 meters, significantly improving reception compared to the built-in antenna with −88 dBm.